High Isolation Auxiliary Power Source for High Voltage Converters Employing Wireless Inductive Power Transfer - Leonardo F. Pacheco; Gustavo C. Bernardi; Andre L. Kirsten (IEEE Access)
A study of a wireless power source operating at high switching frequency to feed gate drivers of high voltage converter switches is presented. Wireless Inductive Power Transfer is chosen for its high isolation between primary and secondary windings, ensuring isolation from control to power circuits. Series-series reactive power compensation is applied due to the low coupling factor, which causes elevated circulation of reactive power and thus losses can be increased. The resonant circuit is powered by a controlled current source instead of a voltage source, ensuring appropriate voltage regulation without a voltage loop control and the need of control signal transmission between primary and secondary windings. A Proportional Resonant control scheme is implemented to apply a sinusoidal input current source, increasing the power factor and reducing reactive power. This paper presents the operation, modeling and control of proposed topology. A prototype with input voltage of 50 V, output voltage of 24 V, rated output power of 100 W and 125 kV isolation between primary and secondary stages was built and its experimental results are included in this paper.